Implementasi Manajemen Pendidikan Akhlak di Mandrasah Aliyah Negeri (MAN) 1 Lombok Timur - Muhamad Zaril Gapari (MANAZHIM, 2019)
Student moral decline, it takes a serious effort from the school to anticipate various forms of student delinquency in school. One way that can be taken is to build students' morals so that they are noble, responsible, strong, and honest personalities, and form strong characters in their lives, especially morals in the form of morality. Efforts to form good morals in students, systematic arrangements are needed, such as teaching management or the learning process. Through the learning process, schools need to pay attention to the development and improvement of mentality in students. Thus, a special management is needed that is developed by the school to improve students' moral quality. For this reason, integrated steps are needed from various parties, both schools, teachers, students, student organizations, and the participation of parents. Based on the description above, this study intends to find out how the implementation program of moral education in students in the context of moral education management applied by East Lombok State Madrasah Aliyah (MAN) 1 is a preventive / repressive effort in dealing with the usual forms of student / teenage delinquency in school and also included outside of school because the most important is also in overcoming the delinquency process. This study uses a qualitative approach. The research subjects were principals, teachers, employees, students, parents of students. While the research informants were principals, teachers, school committees, parents, community leaders, students. Data collection techniques using the method of observation, interviews, and documentation. The data validity technique uses an extension of participation, persistence of observation, triangulation (methods and sources). Data analysis techniques using interactive models consist of data collection, data reduction, data presentation and verification. The results showed that 1) Implementation of management of moral education in students of MAN 1 East Lombok: a) carried out through intraculicular, extracurricular and habituation activities. The implementation of management runs in a structured, integrated and normative manner based on Islamic values, as well as by example. b) The principal in MAN 1 East Lombok has carried out management functions namely planning, organizing, coordinating, directing, monitoring and evaluating.